2012
DOI: 10.1016/j.jtcvs.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and in-hospital mortality in Chinese patients undergoing coronary artery bypass grafting: Analysis of a large multi-institutional Chinese database

Abstract: The risk profiles and in-hospital mortality of Chinese patients undergoing coronary artery bypass grafting were determined from data in the most up-to-date multi-institutional database. Eleven variables were demonstrated to be independent risk factors for in-hospital death after coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…[9,11,23] However, a recent Chinese study still suggested COPD to be an independent risk factor for postoperative mortality after CABG. [24] To further clarify this divergence, the present meta-analysis on this topic of interest was performed.…”
Section: Discussionmentioning
confidence: 99%
“…[9,11,23] However, a recent Chinese study still suggested COPD to be an independent risk factor for postoperative mortality after CABG. [24] To further clarify this divergence, the present meta-analysis on this topic of interest was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACE-I or ARB use before surgery and high BUN levels were associated with worse outcome, in accordance with the findings of previous studies. An observational study using a multicenter registered database of patients who underwent CABG in China revealed that preoperative atrial fibrillation was associated with mortality [23]. The GOPCABE trial also showed that preoperative atrial fibrillation was adversely associated with the combined endpoint, including death, myocardial infarction, dialysis, and revascularization, and even the 30-day mortality rate of CABG patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Significant risk factors included in both the SinoSCORE and derived SinoSCORE model are summarised in table 3 10. Factors that were found to be significant in the original SinoSCORE, but lacked significance in the derived SinoSCORE model included body mass index, preoperative atrial fibrillation, COPD and non-elective surgery.…”
Section: Resultsmentioning
confidence: 99%